Excited state dynamics of DNA bases - Kleinermanns, Karl; Nachtigallová, Dana; de Vries, Mattanjah S. (International reviews in physical chemistry, 2013)
Biochemical reactions are subject to the particular environmental conditions of planet earth, including solar irradiation. How DNA responds to radiation is relevant to human health because radiation damage can affect genetic propagation and lead to cancer and is also important for our understanding of how life on earth developed. A reductionist approach to unravelling the detailed photochemistry seeks to establish intrinsic properties of individual DNA building blocks, followed by extrapolation to larger systems, to incorporate interactions between the building blocks and the role of the biomolecular environment. Advances in both experimental and computational techniques have lead to increasingly detailed insights in the excited state dynamics of DNA bases in isolation as well as the role of the solvent and intermolecular interactions. This review seeks to summarise current findings and understanding.